Optimalisasi Penerapan Standard Operating Procedure Memasuki Enclosed Space (Water Ballast Tank) pada MT. Emmanuel untuk Meminimalisir Kecelakaan Kerja - Mohammad Mahmudhon; Anak Agung Istri Sri Wahyuni; Maulidiah Rahmawati; Tri Haryanto (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Work accidents when entering enclosed spaces (water ballast tank) pose a high risk that can endanger the safety of ship crew. This study aims to identify: 1) the factors causing work accidents during entry into the enclosed space (water ballast tank) on MT. Emmanuel; and 2) efforts to minimize the risk of such accidents. This research was conducted over 12 months during onboard practical training on MT. Emmanuel using fishbone analysis as the data analysis technique. Based on the analysis, accident causes include worker overconfidence, non-compliance with the permit to enter procedures, lack of oxygen and toxic gas monitoring, and poor communication among crew members. Suggested measures to minimize accidents are the regular implementation of safety meetings, internal sanctions for SOP violators, periodic drills for entering hazardous spaces, and disciplined enforcement of the permit to enter in accordance with ISGOTT 5th Edition Chapter 10 standards. The implementation of these steps is expected to improve crew safety and reduce the risk of accidents in enclosed spaces.